Reviews - Huard, Samuel (Religion and society, 2024)
CORWIN, Anna I., Embracing Age: How Catholic Nuns Became Models of Aging Well, 202 pp., bibliography, index. New Brunswick, NJ: Rutgers University Press, 2021. Hardback, $ 150. ISBN: 9781978822283. ANDRÉS, Rafael Ruiz, La secularización en España: Rupturas y cambios religiosos desde la sociología histórica, 328 pp. Madrid: Cátedra, 2022. Paperback, € 15.67 (ISBN: 9788437643908). EPub, € 10.92 (ISBN: 9788437643915). SNODGRASS, Jeffrey, The Avatar Faculty: Ecstatic Transformations in Religion and Video Games, 200 pp., ills., bibliography, index. Oakland: University of California Press, 2023. Hardback, $ 95.00. ISBN: 9780520384354. BERES, Derek, Matthew REMSKI, and Julian WALKER, Conspirituality: How New Age Conspiracy Theories Became a Health Threat, 370 pp., acknowledgments, notes, index. New York: PublicAffairs, 2023. $ 30. ISBN: 9781541702981. COPEMAN, Jacob, Arkotong LONGKUMER, and Koonal DUGGAL, eds., Gurus and Media: Sound, Image, Machine, Text, and the Digital, xvii, 453 pp., 55 color plates, index. London: UCL Press, 2023. Paperback, $ 60. ISBN: 978-18-00-08555-8. GAITANIDIS, Ioannis, Spirituality and Alternativity in Contemporary Japan: Beyond Religion?, xii, 245 pp., 8 b/w ills., 3 graphs, bibliography, index. London: Bloomsbury Academic, 2023. Hardback, $ 115. ISBN: 9781350262614. Paperback, $ 35.95. ISBN: 9781350262652. MOHAN, Urmila, ed., The Efficacy of Intimacy and Belief in Worldmaking Practices, 242 pp., 43 b/w ills. New York: Routledge, 2024. Hardback, £135. ISBN: 9781032498812. E-book, £35.99. ISBN: 9781003409731. ESPÍRITO SANTO, Diana, Spirited Histories: Technologies, Media, and Trauma in Paranormal Chile, 212 pp., 11 b/w ills., bibliography, index. London: Routledge, 2024. Paperback, $ 54.99. ISBN: 9780367691813. PÉREZ, Elizabeth, The Gut: A Black Atlantic Alimentary Tract, 84 pp. Cambridge: Cambridge University Press, 2023. Paperback, £17.00. ISBN: 9781009031530. E-book, £17.00. ISBN: 978-1-009-03311-4. PALMIÉ, Stephan, Thinking with Ngangas: What Afro-Cuban Ritual Can Tell Us about Scientific Practice and Vice Versa, 288 pp. Chicago: University of Chicago Press, 2023. Cloth, $ 99. ISBN: 978-0-226-82592-2. Paperback, $ 30. ISBN: 978-0-226-82594-6. E-book, $ 29.99. ISBN: 978-0-226-82593-9. SUHR, Christian, dir., Light Upon Light. 78 mins. In Arabic, English, and Danish with English and French subtitles, 2023. Available through Documentary Educational Resources.